Seepage Grouting Mechanism for Foundations in Goaf Sites considering Diffusion Paths - Hui Wang; You Li; Zhiyuan Dun; Jianhua Cheng; Zhilin Dun; Chenxi Wu (Geofluids)
Grouting treatment is the main technology to reduce or eliminate the residual deformation and activation deformation of foundations in the goaf sites. Under the influences of the overburden of the mining, the distribution of grouting in goaf foundation is quite different from that of conventional grouting mechanism in porous media. In this paper, considering the time-dependent viscosity and diffusion path of the slurry, the conventional permeation diffusion mechanism of Bingham fluid is derived based on the seepage motion equation in porous media. The theoretical formula is modified according to the fracture distribution characteristics of caving zone and fault zone of the goaf foundation and the superposition effect of porous grouting. Combined with the laboratory test, the theoretical formulas for four working conditions ((i) only considering the time-dependent viscosity, (ii) considering the time-dependent viscosity and diffusion path, (iii) combining the fracture distribution characteristics of goaf foundation, and (iv) combining the fracture distribution characteristics and the superposition effect of porous grouting) are verified, respectively. The results of theoretical formula are used to compare with the design scheme of an engineering example. The research results have an important engineering significance for revealing the mechanism of seepage grouting in goaf foundation and designing the optimal spacing between grouting holes.